21 Renal blood flow measurements by magnetic resonance imaging using arterial spin labelling as a novel non-invasive biomarker in paediatric renal transplant recipients. (4th October 2017) - Marks, SD; Nery, F; Cutajar, M; Clark, C; Thomas, D; Gordon, I
Abstract : Background: To investigate our hypothesis that non-invasive cortical renal blood flow (cRBF) measurements using functional magnetic resonance imaging (MRI) arterial spin labelling (ASL) are sensitive biomarkers of early damage of the transplanted kidney in paediatric renal transplant recipients (pRTR). Methods: Prospective study of pRTR undergoing MRI imaging using 1.5T Siemens Avanto system with multi-TI pulsed ASL acquisition performed at 10–20 days, 2 and 12 months with a FAIR labelling scheme and multi-shot 3D grase imaging module with background suppression. Results: 14 pRTR (50% (7) male) aged 9.2–17.1 (median 13.2) years of whom 64% (9) had end-stage kidney disease due to congenital anomalies of the kidney and urinary tract underwent MRI ASL after transplantation (86% (12) living-related) with estimated glomerular filtration rates of 41.0–92.0 (median 60.9) mls/min/1.73 m 2 at follow-up of 3.5 to 5.4 (median 4.5) years. 46% (6) were pre-emptive transplants with 7% (1) re-transplanted. Patients had 0–5 (median 1) post-transplant urinary tract infections with 50% (7) EBV viraemia and underwent 1–7 (median 2) percutaneous renal transplant biopsies with evidence of steroid-resistant acute rejection episode due to non-adherence and borderline rejection in 7% (1) and 14% (2) pRTR respectively. Baseline MRI ASL at median 10 days showed cRBF of 86–268 (median 198) mls/100 g/min with changes at subsequent and latest MRI performed at median 70 and 344 days respectively of −70 to +121 (median 52) and −56 to +147 (median 36) mls/100 g/min respectively. Conclusions: Renal blood flow maximises in the first month after renal transplantation with subsequent reduction in first year in pRTR. There are multiple causes of renal allograft dysfunction in pRTR and associated risks in performing surveillance percutaneous renal transplant biopsies. MRI ASL is a useful and novel non-invasive biomarker of renal allograft function in pRTR.